2020
DOI: 10.3389/fmicb.2020.569366
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation With the Plant-Growth-Promoting Rhizobacterium Pseudomonas fluorescens LBUM677 Impacts the Rhizosphere Microbiome of Three Oilseed Crops

Abstract: The bacterial communities inhabiting the rhizosphere play an important role in plant development and health. Here we studied the effect of inoculation with Pseudomonas fluorescens LBUM677, a plant growth promoting rhizobacterium that promotes seed oil accumulation, on the rhizosphere microbiome of three oilseed crops ( Brassica napus , Buglossoides arvensis , and Glycine max ) over time. Next-Generation high-throughput … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 80 publications
1
6
0
2
Order By: Relevance
“…These findings contrast with previous studies showing minor and/or transient ecological impact of Azospirillum inoculants on the resident bacterial community colonizing the rhizosphere ( Ambrosini et al, 2016 ), by molecular fingerprinting in the case of maize ( Herschkovitz et al, 2005 ; Lerner et al, 2006 ; Matsumura et al, 2015 ), wheat ( Naiman et al, 2009 ; Baudoin et al, 2010 ), rice ( Pedraza et al, 2009 ; García de Salamone et al, 2010 , 2012 ; Bao et al, 2013 ), or other crops ( Correa et al, 2007 ; Felici et al, 2008 ), as well as by Illumina MiSeq metabarcoding in the case of maize ( da Costa et al, 2018 ). Modest inoculant impacts on the rhizobacterial community were also found with Bacillus on lettuce (by metagenomics; Kröber et al, 2014 ) and tomato (by pyrosequencing; Qiao et al, 2017 ), Pseudomonas on lettuce (by DGGE and pyrosequencing; Schreiter et al, 2014 ), Pseudomonas or Achromobacter on maize (by Illumina MiSeq; da Costa et al, 2018 ), Stenotrophomonas on maize (by Illumina MiSeq; Kusstatscher et al, 2020 ), multispecies inoculants on tomato (by Illumina MiSeq; Nuzzo et al, 2020 ) and wheat (by pyrosequencing; Dal Cortivo et al, 2020 ), or a multispecies organic amendment on sugarcane (by Illumina MiSeq; Berg et al, 2019 ), whereas a larger impact was observed by Illumina MiSeq with Pseudomonas on maize ( Ke et al, 2019 ) and different oilseed crops ( Jiménez et al, 2020 ); Pseudomonas , Paenibacillus , or Bacillus on lettuce ( Passera et al, 2020 ); an organic amendment enriched in microorganisms on strawberry ( Deng et al, 2019 ); or a multispecies inoculant on onion ( Pellegrini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings contrast with previous studies showing minor and/or transient ecological impact of Azospirillum inoculants on the resident bacterial community colonizing the rhizosphere ( Ambrosini et al, 2016 ), by molecular fingerprinting in the case of maize ( Herschkovitz et al, 2005 ; Lerner et al, 2006 ; Matsumura et al, 2015 ), wheat ( Naiman et al, 2009 ; Baudoin et al, 2010 ), rice ( Pedraza et al, 2009 ; García de Salamone et al, 2010 , 2012 ; Bao et al, 2013 ), or other crops ( Correa et al, 2007 ; Felici et al, 2008 ), as well as by Illumina MiSeq metabarcoding in the case of maize ( da Costa et al, 2018 ). Modest inoculant impacts on the rhizobacterial community were also found with Bacillus on lettuce (by metagenomics; Kröber et al, 2014 ) and tomato (by pyrosequencing; Qiao et al, 2017 ), Pseudomonas on lettuce (by DGGE and pyrosequencing; Schreiter et al, 2014 ), Pseudomonas or Achromobacter on maize (by Illumina MiSeq; da Costa et al, 2018 ), Stenotrophomonas on maize (by Illumina MiSeq; Kusstatscher et al, 2020 ), multispecies inoculants on tomato (by Illumina MiSeq; Nuzzo et al, 2020 ) and wheat (by pyrosequencing; Dal Cortivo et al, 2020 ), or a multispecies organic amendment on sugarcane (by Illumina MiSeq; Berg et al, 2019 ), whereas a larger impact was observed by Illumina MiSeq with Pseudomonas on maize ( Ke et al, 2019 ) and different oilseed crops ( Jiménez et al, 2020 ); Pseudomonas , Paenibacillus , or Bacillus on lettuce ( Passera et al, 2020 ); an organic amendment enriched in microorganisms on strawberry ( Deng et al, 2019 ); or a multispecies inoculant on onion ( Pellegrini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The massive release of BCAs has been hypothesized to have an impact on the plant microbiome. Low-throughput methods at first (plating, DGGE, FISH, Sanger sequencing) and high-throughput methods recently (next-generation sequencing) have analyzed the rhizosphere, and secondarily the phyllosphere microbiota following BCA application [ 133 , 134 ]. Overall, it appears that bacterial BCAs have a minor and transient effect on the microbiome after soil application [ 135 , 136 , 137 , 138 , 139 , 140 ], independently of the soil type and properties [ 141 , 142 , 143 , 144 , 145 ].…”
Section: Shifting Perspectives In Bca Mode Of Action and Applicationmentioning
confidence: 99%
“…PGPB рода Pseudomonas синтезируют метаболиты, оказывающие ростостимулирующее и антифунгальное действие на растения (5)(6)(7)(8)(9). При использовании этих биопрепаратов показан прирост биологического и хозяйственного урожая ряда культур (7,8).…”
unclassified
“…PGPB рода Pseudomonas синтезируют метаболиты, оказывающие ростостимулирующее и антифунгальное действие на растения (5)(6)(7)(8)(9). При использовании этих биопрепаратов показан прирост биологического и хозяйственного урожая ряда культур (7,8). Интерес вызывают препараты, созданные на базе совместных культур двух и более PGPB, в частности микробиологический продукт на основе Pseudomonas aureofaciens и Azotobacter vinelandii (10)(11)(12)(13).…”
unclassified